2000
DOI: 10.1063/1.1325394
|View full text |Cite
|
Sign up to set email alerts
|

Low-dislocation-density GaN from a single growth on a textured substrate

Abstract: (Received s The density of threading dislocations (TD) in GaN grown directly on flat sapphire substrates *m is typically greater than 109/cm2. Such high dislocation densities degrade both the electronic so and photonic properties of the material. The density of dislocations can be decreased b~~@ orders of magnitude using cantilever epitaxy (CE), which employs prepattemed sapphire substrates to provide reduced-dmension mesa regions for nucleation and etched trenches ($)42 between them for suspended lateral grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(85 citation statements)
references
References 16 publications
0
85
0
Order By: Relevance
“…7,8 After deposition and annealing of a thin GaN nucleation layer and deposition of a thin GaN layer at 1050°C, the GaN growth temperature is decreased to 950°C to produce pyramidal facets (112-2) on top of the sapphire line. After the pyramidal facets are well formed, the GaN, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7,8 After deposition and annealing of a thin GaN nucleation layer and deposition of a thin GaN layer at 1050°C, the GaN growth temperature is decreased to 950°C to produce pyramidal facets (112-2) on top of the sapphire line. After the pyramidal facets are well formed, the GaN, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such high dislocation densities degrade both the electronic and photonic properties of the material. The density of dislocations can be decreased by orders of magnitude using cantilever epitaxy (CE) [1] , which employs prepatterned sapphire substrates to provide reduced-dimension mesa regions for nucleation and etched trenches between them for suspended lateral growth of GaN or AlGaN. The substrate is prepatterned with narrow lines and etched to a depth that permits coalescence of laterally growing III-N nucleated on the mesa surfaces before vertical growth fills the etched trench.…”
Section: Cantilever Epitaxy: a Methods For Low-dislocation-density Ganmentioning
confidence: 99%
“…Cantilever Epitaxy (CE) was invented at Sandia just before the initiation of this program [1]. This prior work showed that greatly reduced dislocation densities were possible with this method.…”
Section: I-b Cantilever Epitaxymentioning
confidence: 99%
“…After some initial tests we also decided to add emissivity correction to this pyrometer, using the basic approach described by Breiland [1]. Some aspects of the hardware and software are different for the…”
Section: Development Of Uv Pyrometer At Sandiamentioning
confidence: 99%